2020
DOI: 10.1136/bmjopen-2019-036659
|View full text |Cite
|
Sign up to set email alerts
|

Non-conveyance in the ambulance service: a population-based cohort study in Stockholm, Sweden

Abstract: ObjectivesNon-conveyed patients represent a significant proportion of all patients cared for by ambulance services in the western world. However, scientific knowledge on non-conveyance is sparse. Therefore, the aim of this study was to describe the prevalence of non-conveyance, investigate associations and compare patients’ characteristics, drug administration, initial problems and vital signs between non-conveyed and conveyed patients.DesignA population-based retrospective cohort study.SettingThe study settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 25 publications
(47 reference statements)
4
37
1
1
Order By: Relevance
“…The decision-making process for non-conveyance appears to be complex and multifactorial [5]. EMS care providers' higher education level [3,8], EMS arrival time in the evening or at night [3,7,9,10], longer distance to a healthcare facility [7], rural area, younger patient age [3,10,11], low National Early Warning Score (NEWS2), and alcohol use increase the likelihood of nonconveyance [3]. A recent review showed that, after a non-conveyance decision, re-contact with the EMS or the ED, hospitalization and mortality rates varied a lot [5].…”
Section: Introductionmentioning
confidence: 99%
“…The decision-making process for non-conveyance appears to be complex and multifactorial [5]. EMS care providers' higher education level [3,8], EMS arrival time in the evening or at night [3,7,9,10], longer distance to a healthcare facility [7], rural area, younger patient age [3,10,11], low National Early Warning Score (NEWS2), and alcohol use increase the likelihood of nonconveyance [3]. A recent review showed that, after a non-conveyance decision, re-contact with the EMS or the ED, hospitalization and mortality rates varied a lot [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the non-transport group were also significantly younger compared to the total ambulance mission population. Other Nordic studies have described a higher probability of non-transport for women and younger patients [17,13]. On the other hand, a study from the Netherlands found no significant difference for gender, although the non-transport group was significantly younger (mean age 48.5 years vs 60.7 years for all missions) [16].…”
Section: Occurrence Of Non-transport Ambulance Missionsmentioning
confidence: 92%
“…A recent systematic review that included studies from North America, Europe, Australia, Asia, and Africa reported that non-transport rates varied from 4% to 94% [7]. Other studies have found non-transport rates of 40% in Finland [14], 38% in the UK [15], 26.2% in Netherlands [16], 15.5% in Australia [8], 13.8% in Sweden [17], and 12.9% in Denmark [18]. Comparatively, the non-transport rate in our study is low.…”
Section: Occurrence Of Non-transport Ambulance Missionsmentioning
confidence: 99%
“…The study area had a population of approximately 2.2 million inhabitants [17]. The ambulance service is a publicly funded health care service, and approximately 210,000 ambulance assignments are performed annually, of which 14% ends in non-conveyance [18]. The ambulance service can be reached through the national emergency number (112), and all ambulance assignments are dispatched by the regional emergency medical communication centre.…”
Section: Settingmentioning
confidence: 99%